ARCHEOGRAPHIC STUDIES IN DAGESTAN IN 2015 - Sihsaidov, A R; Orazaev, G M-R; Navruzov, A R; Zakariaev, Z S; Sehmagomedov, M G; Malamagomedov, D M; Hanmurzaev, I I (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the field archeographic studies, which in 2015 were conducted in a number of mountainous and flat districts of Dagestan to reveal new collections of manuscripts and early printed books, written mostly in Arabic, as well as in the Turkic and Dagestan languages using the Arabic script. One new previously unknown manuscript collection was revealed in Akushinsky district, one collection – in Shamilsky district, six collections – in Karabudakhkentsky district and six collections – in Buinaksky district – a total of 14 collections of more than 470 units of description.